2012
DOI: 10.1055/s-0031-1298432
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of the Absolute Configuration of Twelve Monosaccharide Enantiomers from Natural Products in a Single Injection by a UPLC-UV/MS Method

Abstract: In natural product chemistry, it is often crucial to determine sugar composition as well as the absolute configuration of each monosaccharide in glycosides. An ultra-performance liquid chromatography method using both photodiode array (PDA) and mass spectrometry detectors (UPLC-UV/MS) was developed for qualitative analysis of the absolute configuration of monosaccharide enantiomers. Within a single injection, 16 monosaccharide derivatives including 6 pairs of aldose enantiomers (D/L-glucose, D/L-galactose, D/L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 6 publications
0
57
0
Order By: Relevance
“…Other HMBC peaks allow for the assignment of the carbons within the aglycone, which have been well described in the literature. [12,18] Using an established HPLC method, [14,15] the sugars were both found to be the D-enantiomer (UPLC profile of the standard sugars and the sugars from 1 can be found in the Supporting information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other HMBC peaks allow for the assignment of the carbons within the aglycone, which have been well described in the literature. [12,18] Using an established HPLC method, [14,15] the sugars were both found to be the D-enantiomer (UPLC profile of the standard sugars and the sugars from 1 can be found in the Supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…[12] Sugar enantiomer determination To determine if the attached sugars were D or L, a chromatographic methodology was used. [14,15] The sugars were hydrolyzed from the anthocyanins by heating 4 mg anthocyanin in 1.0 mL of 0.1M HCl for 12 h at 70°C. The sugars were isolated from the anthocyanin aglycones using a C18 cartridge.…”
Section: Nmr Spectramentioning
confidence: 99%
“…A combination of techniques is required. [22] HPAEC-PAD Relatively newly applied to oligosaccharides [24] CE-LIF Amination [32] CE-LIF: Capillary electrophoresis with laser-induced fluorescence; CID: Collision-induced dissociation; HPAEC-PAD: High-pH anion exchange chromatography with amperometric detection.…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al 25 reported a simultaneous enantioseparation of monosaccharides derivatized with L-cysteine methyl ester and phenyl isothiocyanate by ultraperformance liquid chromatography (UPLC) with mass spectrometry, where enantiomeric pairs of three hexoses (Glc, Gal and allose), three pentoses and four deoxy-D-hexoses were simultaneously separated.…”
Section: Introductionmentioning
confidence: 99%